The prevalence of Candida spp. in the saliva of controlled and uncontrolled diabetes mellitus type II patients - Talabani, Alan N; Kim, Chong L; Kiat, Alan O H; Ismail, Abdul Rashid; Chinna, Karuthan (Journal of Baghdad College of Dentistry, 2013)
Background: Diabetes mellitus type 2 has been known for many years as the most common endocrine metabolic disorder that affect the oral cavity and cause many oral diseases including candidiasis. In this study, the incidence of Candida spp. in the saliva of controlled and uncontrolled diabetic patients were determined and compared with non diabetic group. Material and method: The sample consists of 200 subjects: 100 diabetic patients [57 (28.5%) uncontrolled diabetes, 43 (21.5%) controlled diabetes] and 100 (50%) non diabetic groups. Saliva samples was obtained from the subjects and cultured on selective media using appropriate microbiological method to observe the presence of Candida spp. Results: The results revealed a significant association (p < 0.001) between diabetic patients and the presence of Candida spp. using statistical analysis. The odds ratio of the presence of Candida spp. in the controlled and uncontrolled diabetic patients were 0.539 (95% CI= 0.193, 1.508).The odds ratio of the presence of Candida spp. in the uncontrolled and controlled diabetic patients were 17.433 (95% CI= 7.298, 41.642) and 9.40 (95% CI = 4.068, 21.686), respectively, compared to non diabetic group. A significant association was found between the Presence of Candida spp. and the following variables: Groups (p < 0.000), Gender (p < 0.000), Smoking (p < 0.000), Antibiotics (p < 0.000), oral mouthwash (p < 0.000) Edentulous (p < 0.000) and Denture wearing (p < 0.000). Conclusion: Candida spp. population significantly increased in the oral flora of diabetic patients compared with non diabetic group.